The California Consumer Privacy Act (CCPA) : an implementation guide - Bukaty, Preston (IT Governance Publishing, 2019)
Established in June 2018, the CCPA was created to remedy the lack of comprehensive privacy regulation in the state of California. The CCPA came into effect on January 1, 2020, and gives California residents the right to: Learn what personal data a business has collected about them ; Understand who this data has been disclosed to ; Find out whether their personal data has been sold to third parties, and who these third parties are ; Opt out of such data transactions, or request that the data be deleted. Many organizations that do business in the state of California must align to the provisions of the CCPA. Much like the EU's GDPR (General Data Protection Regulation), businesses that fail to comply with the CCPA will face economic penalties.--